Impact of overweight and obesity on the clinical course of bronchial asthma in children - A.V. Kupkina (Zaslavsky O.Yu., 2020)
Background. At present, the question of the influence of overweight and obesity on the clinical course of bronchial asthma in children remains poorly understood and requires further research. The purpose of the research is to study the clinical features of bronchial asthma in overweight and obese children. Materials and methods. A study of 94 patients with bronchial asthma in children aged 6 to 18 years was conducted. Depending on the body mass index, patients were divided into the following clinical groups: 30 children with normal weight, 45 children with overweight and 19 children with obesity. Research methods clinical were as follows: anthropometry, laboratory testing, questionnaire (ACT bronchial asthma control questionnaire). Statistical processing of the obtained data was performed using the statistical package IBM SPSS Statistics Base (version 22) and EZR software version 1.32, graphical interface of the environment R (version 2.13.0). Results. It was found that children in the groups of overweight and obesity are characterized by an early onset of asthma (3 [3; 4] years) with a long persistent nature of the disease. For all three groups, the most common complaints were cough (in the group of normal weight - dry cough (83.3 ± 7.4 %), and in groups with overweight and obesity - wet (66.7 ± 7.0 and 73.7 ± 10.1 %, respectively) and shortness of breath during exercise: the group of normal weight - 46.7 ± 9.1 %, overweight - 82.2 ± 5.7 %, and obesity - 100 %. Complaints of nocturnal asthma attacks were common in 68.9 ± 6.9 and 73.3 ± 10.1 % in the groups of overweight and obesity, respectively. The results of χ2 test showed statistically significant differences between the three groups χ2(2) = 15.947; p < 0.001 for this indicator. Severe asthma was more common (70.0 ± 10.5 %) in obese patients, and statistically significant differences were found between the three groups in the test χ2(2) = 5.2463, p < 0.001. Uncontrolled asthma was statistically significant in the group of obese children. There was a statistically significant difference between different- weight groups by the need for bronchodilators H(2) = 40.756, p < 0.001, and the number of nocturnal asthma attacks H(2) = 17.803, p < 0.001. Conclusions. Our study demonstrates the aggravating effect of excess body weight and obesity on the clinical course of bronchial asthma in children, which may be the basis for the correction of asthma therapy in such patients.